Mathematical data processing according to digital image correlation method for polymer composites - Elena M. Strungar; Dmitrii S. Lobanov (Fracture and Structural Integrity)
The paper analyses the numerical algorithms for experimental data processing using a contactless video system Vic-3D, designed for three-dimension analysis of displacement and strain fields, and digital image correlation method. The authors considered methodological issues of conducting an experiment using a video system. They suggested recommendations on the choice of parameters of calculation of correlation, the size of subset and step during the analysis of non-homogeneous displacement and strain fields in polymer composite materials through laminated fiberglass composite. The efficient parameters of mathematical data processing are identified according to digital image correlation method on the basis of building fields for one frame on the surface of laminated fiberglass reinforced plastic at various subset values and at fixed step value. The paper shows the impact of step value on the strain fields detail degree. The authors have identified the relation of the chosen parameters of experimental data processing using digital image correlation method with the scaled levels of consideration of composite materials strain processes. To evaluate the strains at various scale levels, the paper uses supplementary video system instruments: virtual extensometer, rectangular area and line. The authors obtained a longitudinal strain profile that allows evaluating the location of strain peak areas on the composite object surface.